Advanced Rectifier Technologies for Electrolysis-Based Hydrogen Production: A Comparative Study and Real-World Applications - Yan Gao; Xiongzheng Wang; Xin Meng (Energies)
In response to the growing significance of hydrogen as a clean energy carrier, this study investigates the advanced rectifier technologies employed in electrolytic hydrogen production. First, the topologies of three rectifiers typically employed in industry—24-pulse thyristor rectifiers, insulated gate bipolar transistor (IGBT) rectifiers, and 24-pulse diode rectifiers with multi-phase choppers—are described in detail. Subsequently, at a constant 5 MW power level, the three rectifiers are compared in terms of rectifier efficiency, grid-side power quality, power factor, and overall investment cost. The results indicate that in comparison to the other two rectifiers, the thyristor rectifier provides superior efficiency and cost advantages, thereby maintaining a dominant market share. Additionally, case studies of rectifier power supplies from three real-world industrial projects are presented, along with actual grid-side power quality data. Finally, the challenges, potential applications, and future prospects of rectifiers in renewable energy-based hydrogen production are discussed and summarized.